2005
DOI: 10.1159/000083692
|View full text |Cite
|
Sign up to set email alerts
|

Early Diabetes-Related Complications in Adolescents

Abstract: Micro- and macrovascular complications account for the major part of the morbidity and mortality associated with diabetes developing in childhood. Although advanced complications are exceptionally rare in the adolescent age group, it is during this phase that the progression of risk may accelerate. A number of potentially important factors have been identified which might contribute to risk of complication development: some provide insights into the genetics of these complications, while others are potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 132 publications
(114 reference statements)
0
27
1
Order By: Relevance
“…As reported in patients with diabetes, 21 we expected renal injury to occur in the second decade after the onset of glomerular hyperfiltration. Surprisingly, our results illustrate that patients show signs of renal injury during the full age range of childhood.…”
Section: Discussionmentioning
confidence: 87%
“…As reported in patients with diabetes, 21 we expected renal injury to occur in the second decade after the onset of glomerular hyperfiltration. Surprisingly, our results illustrate that patients show signs of renal injury during the full age range of childhood.…”
Section: Discussionmentioning
confidence: 87%
“…In people with childhood-onset T1D, MA is often detected during puberty [7], with a cumulative prevalence of around 10-25% after 5-10 years of diabetes duration [24][25][26] and up to 50% after 19 years of diabetes duration [26]. This is significantly higher than the prevalence of 34% reported in adult cohorts after a similar diabetes duration and exposure to similar levels of glycemic control [15].…”
Section: Diabetic Nephropathymentioning
confidence: 89%
“…Microvascular complications are virtually always subclinical during childhood and adolescence, and advanced stages are extremely rare [7]. However, early signs of microvascular disease, such as increases in albumin excretion rates and glomerular filtration rate (GFR), renal hypertrophy, changes in the retinal microvasculature and impaired autonomic nervous system function, are detectable early during the course of childhood-onset diabetes and often accelerate during puberty.…”
Section: Microvascular Complications Of T1dmentioning
confidence: 99%
“…Nephropathy is the leading cause of chronic renal failure worldwide and is responsible for renal failure in about one third of patients who undergo dialysis. It is suggested that patients with common risk factors including greater duration of diabetes, hypertension, poor metabolic control, smoking, obesity and hyperlipidemia are more prone to develop diabetic complications [7] . In a retrospective study done by Klag et al [8] it was found that elevations of blood pressure are a strong independent risk factor for endstage renal disease and that interventions to prevent the disease need to emphasize the prevention and control of both highnormal and high blood pressure.…”
Section: Risk Factors For Development Of Diabetic Complicationsmentioning
confidence: 99%